Combining sensory evaluations and experimental auctions to assess consumers' preferences for fresh fruit quality characteristics. Issue 2 (19th November 2017) - Gallardo, R. Karina; Hanrahan, Ines; Yue, Chengyan; McCracken, Vicki A.; Luby, James; McFerson, James R.; Ross, Carolyn; Carrillo‐Rodriguez, Lilian
Abstract: A combination of sensory evaluation and experimental auctions was used to analyze consumer preferences for external and internal quality characteristics of two fresh apple varieties "Honeycrisp" and "Gala." A group of 384 panelists in three locations in the United States evaluated the appearance, the internal quality characteristics, in three sequential rounds, for the two apple variety samples. Each panelist responded to a sensory evaluation questionnaire, and then bid on the samples in an incentive compatible second price auction. We found that panelists' bids increased with the amount of information given. Also, we found that for some attributes such as sweetness, panelists preferred levels closer to their ideal rather than objectively measured higher levels. When evaluating consumers' preference and valuation for different fresh fruit varieties, a greater explanatory power is obtained when including an indicator variable for the variety along with the set of quality attributes. The indicator variable could improve the control of inherent factors related with the varieties but cannot be observed or inferred easily. Finally, our findings add to previous studies in that flavor, when expressed as a combination of sweetness and acidity in addition to textural attributes, are important determinants of consumers' acceptance. [EconLit citations: Q13]